Sustainable Tourism Challenges and Opportunities: Development of North Rupat Island, Bengkalis Regency - Eka, Eka; Sukristyanto, Agus; Saputra, Trio (LPPM Universitas PGRI Sumatera Barat, 2025)
Tourism plays a vital role in driving economic growth, particularly in remote island regions such as North Rupat Island, Bengkalis Regency. Despite its designation as a National Tourism Strategic Area under the 2011–2025 master plan, the progress of sustainable tourism development in this area remains limited. This study adopts a qualitative case study approach to assess the implementation of sustainable tourism principles. Data were collected through purposive sampling, including in-depth interviews, field observations, and analysis of local government planning documents. Thematic analysis was employed to evaluate the application of nine core principles of sustainable tourism. Findings reveal that implementation is only partial. Government-led training initiatives and community participation through tourism awareness groups are evident; however, critical challenges persist, such as inadequate infrastructure, unmanaged waste, limited community control over land, and weak enforcement of environmental regulations. Furthermore, local aspirations for improved road access remain unfulfilled, restricting tourism potential and economic benefits for residents. The study highlights a significant gap between national-level planning and local-level execution, underscoring the need for stronger integration among stakeholders. This research contributes by identifying key barriers and enabling factors for sustainable tourism and emphasizes the importance of inclusive, community-centered strategies tailored to island-based tourism contexts